Determinants of Indoor NO2 and PM2.5 Concentration in Senior Housing with Gas Stoves - Khafayat Kadiri; David Turcotte; Rebecca Gore; Anila Bello; Susan R. Woskie (Toxics)
Nitrogen dioxide (NO2) and particulate matter of 2.5 microns (PM2.5) are air pollutants that impact health, especially among vulnerable populations with respiratory disease. This study identifies factors influencing indoor NO2 and PM2.5 in low-income households of older adults with asthma who use gas stoves in Lowell, Massachusetts. Environmental sampling was conducted in 73 homes, measuring NO2, PM2.5, fractional stove-use, temperature, and humidity for 5–7 days. Participants were recruited between December 2020 and July 2022. Questionnaires were used to collect data on factors influencing indoor NO2 and PM2.5 concentrations. Daily outdoor NO2 and PM2.5 concentrations were obtained from a United States Environmental Protection Agency (EPA) monitoring station. Paired t-tests were conducted between indoor and outdoor NO2 and PM2.5 concentrations, and linear regression was used to evaluate factors influencing indoor NO2 and PM2.5 concentrations. The average indoor concentration for NO2 and PM2.5 were 21.8 (GSD = 2.1) ppb and 16.2 (GSD = 2.7) µg/m3, respectively. Indoor NO2 and PM2.5 concentrations exceeded outdoor concentrations significantly. In multiple regression models, season and pilot light stove use significantly predicted indoor NO2. Season and air freshener use for 6–7 days/week significantly predicted indoor PM2.5. Season-influenced higher indoor concentrations are likely due to reduced ventilation in colder months in the Northeast U.S.